Transforming growth factor beta specifically enhances IgA production by lipopolysaccharide-stimulated murine B lymphocytes (The Rockefeller University Press, 1989)
The addition of TGF-beta to cultures of LPS-stimulated murine B cells causes a approximately 10-fold enhancement of IgA production, yet causes a 10-fold decrease in total Ig production. IL-2 and, to a lesser extent, IL-5 synergize with TGF-beta to further enhance IgA production and partially reverse the inhibition of total Ig production. IgA constitutes only approximately 0.1% of total Ig in LPS-stimulated cultures, but that percentage rises to 15-25% in cultures to which TGF- beta and IL-2 are added. TGF-beta induces a substantial increase in IgA production from sIgA- B cells but inhibits IgA production by sIgA+ cells. This finding suggests that TGF-beta acts as an isotype-specific switch factor for IgA.